1996
DOI: 10.1073/pnas.93.13.6291
|View full text |Cite
|
Sign up to set email alerts
|

Gene gun-mediated skin transfection with interleukin 12 gene results in regression of established primary and metastatic murine tumors.

Abstract: Particle-mediated (gene gun) in vivo delivery of the murine interleukin 12 (IL-12) gene in an expression plasmid was evaluated for antitumor activity. Transfer of IL-12 cDNA into epidermal cells overlying an implanted intradermal tumor resulted in detectable levels (266.0 ± 27.8 pg) of the transgenic protein at the skin tissue treatment site. Despite these low levels of transgenic IL-12, complete regression of established tumors (0.4-0.8 cm in diameter) was achieved in mice bearing Renca, MethA, SA-1, or L5178… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
165
0
2

Year Published

1997
1997
2010
2010

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 234 publications
(172 citation statements)
references
References 28 publications
5
165
0
2
Order By: Relevance
“…These cytokines were repeatedly shown to exhibit functional biological activity, as many researchers have previously reported. 22,29,30 A comparison of the results from our current study versus those reported by Rajagopalan and Malter 22 suggests that 3 0 cDNA structural features may influence transgenic protein expression via additional mechanisms besides mRNA stability and polysome-run-on efficiency. It is currently unclear to us as to which mechanism(s) (eg, RNA stability) is playing the key role for enhanced cytokine gene expression, and additional experiments are needed to demonstrate the possible post-transcriptional, translational or other processing regulations of these transgenic RNA or DNA vector systems.…”
Section: Introductionsupporting
confidence: 55%
See 3 more Smart Citations
“…These cytokines were repeatedly shown to exhibit functional biological activity, as many researchers have previously reported. 22,29,30 A comparison of the results from our current study versus those reported by Rajagopalan and Malter 22 suggests that 3 0 cDNA structural features may influence transgenic protein expression via additional mechanisms besides mRNA stability and polysome-run-on efficiency. It is currently unclear to us as to which mechanism(s) (eg, RNA stability) is playing the key role for enhanced cytokine gene expression, and additional experiments are needed to demonstrate the possible post-transcriptional, translational or other processing regulations of these transgenic RNA or DNA vector systems.…”
Section: Introductionsupporting
confidence: 55%
“…The quantity of transgenic murine IL-12 protein heterodimer was determined by a cell proliferation bioassay using ConA-activated splenocytes, as previously described. 30 Human IL-12 levels were determined via a p35/p40 heterodimer-specific ELISA kit (R&D Systems, Minneapolis, MN, USA). Based on results from this study, we estimate that an increase of at least seven to 30-fold in various cytokine transgene expression levels could be readily obtained by employing a combination of such molecular strategies for vector, promoter or other sequence constructions.…”
Section: Optimization Of Concomitant/coordinated Expression Of Two Sumentioning
confidence: 99%
See 2 more Smart Citations
“…These include injection of genetically engineered fibroblasts for the secretion of IL-12 in an orthotopic melanoma model; direct transfer of IL-12 cDNA via gene gun-mediated transfection of skin tissue overlaying subcutaneous melanomas; direct intratumoral injection of adenovirus expressing IL-12 in ectopic breast and colon cancer models; and intradermal injection of IL-12 cDNA and vaccination using irradiated IL-12-transfected tumor cells in a metastatic colon cancer model. [15][16][17][18][19][20][21] These models suggest that IL-12 gene therapy results in tumor regression and suppression of metastasis.…”
Section: Introductionmentioning
confidence: 99%